2017
DOI: 10.1007/s10753-017-0716-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Sensitizes the HaCaT Cells to the IFN-γ Pathway and Downregulates MDC, ICAM-1, and SOCS1 by Activating p38, JNK, and Akt

Abstract: Decreased interferon (IFN)-γ levels and increased levels of macrophage-derived chemokine (MDC) and intercellular adhesion molecule (ICAM)-1 are known to be involved in allergic skin diseases, such as eczema and atopic dermatitis. Activation of the IFN-γ and its downstream interleukin-12 (IL-12) pathway can correct these diseases. Suppressor of cytokine signaling 1 (SOCS1) is a cytokine signaling inhibitor that blocks downstream pathways of IFN-γ by blocking the mitogen-activated protein kinase (MAPK) and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…MMP9 may be directly related to the pathogenesis and development of eczema, as it may affect the susceptibility to eczema by degrading COL5A3 [36]. Moreover, the downregulation of ICAM-1 and AKT expression via activation of MAPK8 and JNK has been shown as one of the mechanisms in the treatment of eczema [37]. These targets play an important role in the pathogenesis of eczema; thus, drug interventions targeting these genes can be effective for eczema treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 may be directly related to the pathogenesis and development of eczema, as it may affect the susceptibility to eczema by degrading COL5A3 [36]. Moreover, the downregulation of ICAM-1 and AKT expression via activation of MAPK8 and JNK has been shown as one of the mechanisms in the treatment of eczema [37]. These targets play an important role in the pathogenesis of eczema; thus, drug interventions targeting these genes can be effective for eczema treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that pathological cell adhesion is observed between nerve fibers and mast cells in AD skin lesions [ 37 ]. ICAM-1, VCAM-1, and selectins are closely related to allergic skin diseases and their levels are consequentially increased in the epidermis of patients with AD; Th2 cytokines are recruited to the inflamed site by these inflammatory factors [ 38 ]. In the present study, we found that HT treatment reduced the protein levels of adhesion molecules in Dfb-induced AD mice model ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OMT accelerates cancer cell apoptosis and reverses multidrug resistance when combined with other chemotherapeutic drugs . The anti‐inflammation effects of OMT appear to involve both inhibition of MAPK phosphorylation and reduce the activation of the NF‐κB signalling pathway . Furthermore, OMT exhibits substantial therapeutic potential for the treatment of myocardial diseases through modulating of the JAK2/STAT3 and TGF‐β1/Smad3 signalling pathway, but the effects of OMT on the onset and progression of OA have not been reported, to our knowledge.…”
Section: Introductionmentioning
confidence: 90%